PENERAPAN METODE PROBLEM BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL - Cicilia Melinda; Ilham Rahmawati (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2021)
Critical thinking skills need to be instilled in the learning process in junior high schools. In this case, a teaching method that can improve students' critical thinking skills, namely the problem based learning method, is needed. The purpose of this study was to examine whether problem based learning method was able to improve the critical thinking skill of students in junior high school in the subjects of Social Sciences. The research method is quantitative. The research instrument used a test at the beginning and end of learning. The data collecting technique used test. The data analysis of this study used a partial test. The results showed that the problem based learning method had an influence on the critical thinking skills of students with t table 3, 902 t count 1.669. Thus, there is an effect of the problem based learning method on the critical thinking skills of junior high school students.